THE INFLUENCE OF GOOD CORPORATE GOVERNANCE, REGIONAL ORIGINAL INCOME, GENERAL ALLOCATION FUNDS, CAPITAL EXPENDITURE AND COMMUNITY WELFARE ON ECONOMIC GROWTH IN GRESIK DISTRICT - Allen Pranata Putra; Adam Rio (Fakultas Ekonomi dan Bisnis Universitas Wijaya Putra, 2022)
This research uses variables, namely Good Corporate Governance, Original Regional Income, General Allocation Funds, Capital Expenditures and Community Welfare. In terms of method, this research uses a quantitative approach, the sample taken was 100 respondents spread across officials in Gresik district. This research uses validity tests, classical assumption tests, normality tests. The research results show that the Good Corporate Governance variable has an influence on Economic Growth, then the Regional Original Income variable has a significant influence and the General Allocation Fund variable has a significant influence on economic growth, the capital expenditure variable has no influence on Economic Growth. The Community Welfare variable has no influence on Economic Growth in Gresik Regency.